PN AND SN TOMOGRAPHY ACROSS EURASIA TO IMPROVE REGIONAL SEISMIC EVENT LOCATIONS - Ritzwoller M.H.; Barmin M.P.; Villaseñor A.; Levshin A.L.; Engdahl E.R. (My University, 2002)
This paper has three motivations: first, to map Pn and Sn velocities beneath most of Eurasia to reveal information on a length scale relevant to regional tectonics, second, to test recently constructed 3-D mantle models and, third, to develop and test a method to produce Pn and Sn travel time correction surfaces which are the 3-D analogue of travel time curves for a 1-D model. Our third motive is inspired by the need to improve regional location capabilities in monitoring nuclear treaties such as the nuclear Comprehensive Test Ban Treaty (CTBT). To a groomed version of the ISC/NEIC data, we apply the tomographic method of Barmin et al. [Pure Appl. Geophys. (2001)], augmented to include station and event corrections and an epicentral distance correction. The Pn and Sn maps are estimated on a 1°×1° grid throughout Eurasia. We define the phases Pn and Sn as arriving between epicentral distances of 3° and 15°. After selection, the resulting data set consists of about 1,250,000 Pn and 420,000 Sn travel times distributed inhomogeneously across Eurasia. The rms misfit to the entire Eurasian data set from the Pn and Sn model increases nearly linearly with distance and averages about 1.6 s for Pn and 3.2 s for Sn, but is better for events that occurred on several nuclear test sites and for selected high-quality data subsets. The Pn and Sn maps compare favorably with recent 3-D models of P and S in the uppermost mantle and with recently compiled teleseismic station corrections across the region. The most intriguing features on the maps are the low-velocity anomalies that characterize most tectonically deformed regions such as the anomaly across central and southern Asia and the Middle East that extends along a tortuous path from Turkey in the west to Lake Baikal in the east. These anomalies are related to the closing of the Neo-Tethys Ocean and the collision of India with Asia. The uppermost mantle beneath the Pacific Rim back-arc is also very slow, presumably due to upwelling that results from back-arc spreading, as is the Red Sea rift, the Tyrrhenian Sea and other regions undergoing active extension.